Effect of altered innervation and thyroid hormones on myosin heavy chain expression and fiber type transitions: a mini-review - Soukup, Tomáš; Smerdu, Vika (Histochemistry and cell biology, 2015)
In this mini-review, we briefly present the data regarding the effect of extrinsic factors, i.e., innervation and thyroid hormones (TH) on myosin heavy chain genes and isoforms expression and consequently on muscle fiber type transitions. It has been well known that reduced neuromuscular activity, hyperthyroidism or mechanical unloading stimulate slow-to-fast fiber type transitions, while increased neuromuscular activity, hypothyroidism and higher mechanical loading result in fast to slow fiber type transitions. As there is a plethora of results on these topics, we focus mostly on data relevant to our experimental model of slow-to-fast muscle transformation following heterochronous intramuscular isotransplantation in rats with altered TH status.
Keywords: Rats; zvířata; regulace genové exprese; krysa rodu Rattus; Myosin Heavy Chains; Gene Expression Regulation; těžké řetězce myosinu; Animals; Thyroid Hormones; hormony štítné žlázy; protein - isoformy; Protein Isoforms